Association Between the Individual and Combined Effects of the GSTM1 and GSTT1 Polymorphisms and Risk of Leukemia: A Meta-Analysis - Hu, Ting; Zhou, Guozhong; Li, Wenjin (Frontiers in Genetics, 2022)
Background: Fourteen meta-analyses reported the individual effects of the GSTM1 and GSTT1 polymorphisms with leukemia risk. However, over forty studies did not be included in previously published meta-analyses. Moreover, one key question was that previous meta-analyses did not conduct the false positive test on the above issues. Furthermore, previous meta-analyses did not perform the combined effects of GSTM1 present/null and GSTT1 present/null polymorphism with leukemia risk. Therefore, we conducted the current study to further analyzed these associations. Objectives: To investigate the association between the Individual and combined effects of the GSTM1 present/null and GSTT1 present/null polymorphisms and risk of leukemia Methods: A meta-analysis was performed applying Meta-analyses of Observational Studies in Epidemiology (MOOSE) guidelines. Moreover, False-positive report probability (FPRP) and Bayesian false discovery probability (BFDP) were applied to investigate the false positive results. Results: The individual GSTM1 and GSTT1 null genotypes and combined effects of the two genes was associated with a significantly increased leukemia risk in overall and several subgroup analyses, such as Asians, Caucasians, and so on. Then, further analysis was conducted using FPRP and BFDP. Significant associations were considered as “positive” results on the GSTM1 null genotype with leukemia risk in overall populations (FPRP < 0.001 and BFDP = 0.006), Asians (FPRP < 0.001 and BFDP < 0.001), and East Asia population (FPRP < 0.001 and BFDP = 0.002). For the GSTT1 null genotype, significant associations were regarded as “positive” results in overall populations, acute myeloid leukemia (AML), Asians, and East Asia population. For the combined effects of the GSTM1 and GSTT1 polymorphisms, significant associations were also considered as “positive” results in overall analysis, Asians, Indians, and East Asia populations. Conclusions: This study strongly indicates that the individual GSTM1 and GSTT1 null genotypes and combined effects of the two genes are associated with increased leukemia risk in Asians, especially in East Asia population; the GSTT1 null genotype is associated with increased AML risk; the combined effects of the two genes are associated with increased leukemia risk in Indians.